A importância da análise da culpabilidade como limite à expansão de um novo modelo penal de ocasião - Rocha, Patrícia Vieira de Melo Ferreira (2018)
The 1988 Federal Constitution adopted a guarantor criminal model, which is based on the rule of law, which lists fundamental rights, ensuring the individualization of punishment and establishing limits to the state's punitive power, situations in which guilt plays an important role in maintaining constitutional essence. Regardless of the importance of guilt, it has been suffering a serious crisis generated by the tension between the political-criminal function and the need to determine the proportionality of the penalty applied. The analysis of guilt is now faced not as a constitutional guarantee limiting abuses from the punitive power of the state, but as an obstacle to the application of more severe sentences, giving space to the social need to ward off violence from the social sphere, regardless of the means therefore. In this sense, the satisfaction of the popular clamor for justice gains a prominent place in the criminal jurisdiction, being also adopted as a parameter of efficiency by the Judicial Power. In this context, the concept of justice expected by society is now confused with the maximum application of criminal law, even without compliance with constitutional guarantees. In view of such a scenario, encouraged and propagated by the media, the decisions handed down by the Judiciary Branch are, notably after Criminal Action no. 470/MG, judged by the Federal Supreme Court to follow a new paradigm, utilitarian and with a greater bias corruption and violence aimed at pacification and social welfare, less important if effective mitigation of compliance with the guarantees provided in the constitutional order. A new model of criminal law has been drawn up by the jurisprudence of the STF, which, in order to meet the social anxieties influenced and reverberated by the mass media, makes populist decisions, many in disharmony with the constitutional norm, leaving aside their observance. Constitutional interpretation becomes essential for the maintenance of the constitutional guarantor base, provided it is made according to its essence, rescuing the analysis of guilt, individualizing the sentence, ensuring a subjective judgment of imputation.